2015
DOI: 10.1249/mss.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure Prediction Using Raw Accelerometer Data in Simulated Free Living

Abstract: A single accelerometer placed on the thigh provided the highest accuracy for EE prediction, although monitors worn on the wrists or hip can also be used with high measurement accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 27 publications
5
83
0
Order By: Relevance
“…Though not widely used in physical activity research at present, these methods have demonstrated value for improving estimation of activity intensity over the more common cutpoint methods that rely primarily on less flexible models like linear regression (12,27,30,36).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Though not widely used in physical activity research at present, these methods have demonstrated value for improving estimation of activity intensity over the more common cutpoint methods that rely primarily on less flexible models like linear regression (12,27,30,36).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Some have suggested that simple movement intensity approaches should be replaced by more sophisticated models that utilise a broader range of signal features 40,41 . Recent efforts to estimate energy expenditure have utilised a range of machine learning approaches, such as neural networks 4244 and random forests 40 . While we are not aware of any such methodology with a performance that exceeds the simpler models validated in this paper, this is an interesting area of future work.…”
Section: Discussionmentioning
confidence: 99%
“…While there is robust evidence that physical activity assessment using accelerometry is a good proxy for inferring energy expenditure (e.g. Montoye et al ), there are limitations to these inferences. We did not utilize energy expenditure algorithms available for use with the Actical accelerometer because of ongoing assessment of their accuracy (e.g., Alhassan et al ; Brazeau et al ).…”
Section: Discussionmentioning
confidence: 99%